A compreensão de investigação científica em licenciandos de uma universidade pública do Paraná - Grando, Letícia Manica (2019)
The initial purpose of this study is to analyze if undergraduate students in the last year of Philosophy, Social Sciences, Nursing, Biological Sciences, Chemistry, and Mathematic courses are scientifically informed about the processes involved in a scientific investigation. In order to do that, we utilized as an instrument to constitute the research data, as well as a theoretical and methodological support, the questionnaire The Views About Scientific Inquiry (VASI) developed and validated by Lederman et al. (2014), that contemplates 8 aspects in which, if informed the students’ comprehensions, they can be considered scientifically alphabetized. In addition, we proposed a semi structured interview in part of the subjects with the intention of identifying their comprehensions in respect to the process of scientific investigation, as well as to comprehend the aspects that involve the Nature of Science, the Teaching of Science, and the Approach of Science in their undergraduate courses (which we classify as scientific formation). These comprehensions were categorized according to the theoretical and methodological hypothesis of Content Analysis proposed by Bardin (2016), in which categories and subcategories were formulated. Utilizing these instruments, we tried to investigate if there were differences in the students’ conceptions in relation to Scientific Investigation according to their different areas of graduation, being able to confirm that yes, mainly in the categories that involved comprehensions about the Nature of Science and the Teaching of Science. Trying to figure out if these students can be considered scientifically alphabetized in relation to the comprehension of the processes that occur in a Scientific Investigation, we can consider that some courses have students that comprehend better (informed) some aspects stated by Lederman et al. (2014) while others presented more difficulty in providing scientifically informed comprehensions. In addition to that, it’s worth of mentioning, that no student of the participant courses is scientifically alphabetized in relation to the aspects described by Lederman et al (2014).